ARE DISCIPLINES IN ALL AROUND MEN'S ARTISTIC GYMNASTICS EQUAL - Ivan Čuk; Almir Atiković (Sport Scientific And Practical Aspects, 2025)
On the sample of the 44 gymnasts who competed at the OG 2008 in Beijing in all around, the equality between disciplines was tested. Equality was tested for the achieved A scores on the disciplines of floor exercise, pommel horse, rings, vault, parallel bars and horizontal bar. Vault has the highest A scores, while pommel horse the lowest A scores. T-tests showed that those two disciplines significantly differ from other disciplines in average for 0,4 points. Factor analysis extracted 3 factors, with 67% of explained variance. On the 3rd factor vault on positive side and pommel horse on the negative side were loaded. According to the 2006 Code of points and gymnastics training theory, both have to be revised.